2019
DOI: 10.12948/issn14531305/23.4.2019.06
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Process Automation: Lessons Learned from Case Studies

Abstract: Nowadays, there is a trend in automating repetitive tasks in order to reduce human errors or costs. Digitization asks for new strategies in business processes. Robotic Process Automation (RPA) includes a set of emerging technologies that promises the automation of business processes by using software robots that are trained based on human tasks. Companies need to constantly monitor their own business processes in order to identify and optimize processes suitable for automation. In 2018, Forrester identified Ui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Some feedbacks resulted from interviews with Director to Staff levels that are needed to be further considered are aspects of risk management, policies and changes in habits of human resources. This is also in line with research conducted by Cristina-Claudia OSMAN [3] that companies must continue to monitor all of their business processes in order to identify and optimize the implementation of RPA, including employee involvement in implementing RPA.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Some feedbacks resulted from interviews with Director to Staff levels that are needed to be further considered are aspects of risk management, policies and changes in habits of human resources. This is also in line with research conducted by Cristina-Claudia OSMAN [3] that companies must continue to monitor all of their business processes in order to identify and optimize the implementation of RPA, including employee involvement in implementing RPA.…”
Section: Discussionsupporting
confidence: 81%
“…But the European Patent Office (EPO) recognizes Cyrille Bataller and Adrien Jacquot as the inventors of the RPA. Cyrille Bataller and and Adrien Jacquot define RPA as a technology that makes it possible to automate the implementation of repetitive and intensive activities manually [3]. Gartner has another definition for RPA that RPA is a productivity tool (sold as licensed software) that allows users to configure one or more scripts (the other term is bot) to activate certain key presses in an automatic way [3].…”
Section: Literature Studymentioning
confidence: 99%
See 2 more Smart Citations
“…To get an overview of the commonly applied evaluation approaches, the literature review by Osman (2019) was used as a basis, which collected renowned case studies on RPA implementation. Based on an analysis of these case studies, three methods for the cost-oriented evaluation of RPA implementations can be identified:…”
Section: Automation Of Management Reporting Processesmentioning
confidence: 99%